2019
DOI: 10.5267/j.msl.2019.5.013
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the information quality of local government financial statement and financial accountability

Abstract: The purpose of this paper is to study the effect of internal control system and human resource competence on information quality of local government financial statement and financial accountability. The method of collecting data is questionnaire which is distributed among 161 out of 303 population of employees of the Agency (Dinas) in the Government of South Sumatra Province, Indonesia. The collected data is processed by using SPSS 20.00 with t-test and Path Analysis. The result shows that internal control sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
1
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(102 citation statements)
references
References 11 publications
7
61
1
9
Order By: Relevance
“…Ježovita [49] and Dewi et al [50] study, concluded that relevant financial information in financial reporting is crucial for the decision-making process. Thus, decisionmaking based on financial information provided by accounting, and bringing together all its qualitative characteristics, can determine the Decision-Making Success.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Ježovita [49] and Dewi et al [50] study, concluded that relevant financial information in financial reporting is crucial for the decision-making process. Thus, decisionmaking based on financial information provided by accounting, and bringing together all its qualitative characteristics, can determine the Decision-Making Success.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Kualitas perangkat desa yang baik sangat dibutuhkan dalam melaksanakan tugas dan untuk mewujudkan akuntabilitas dalam pengelolaan keuangan desa (Meutia & Liliana, 2018). Ada tiga kompenen utama dalam membentuk sumber daya manusia yaitu pengetahuan, kompetensi dan perilaku (Dewi et al, 2019). Dalam pengelolaan keuangan yang baik, perangkat desa harus memiliki sumber daya manusia yang berkualitas, didukung dengan latar belakang pendidikan dan pelatihan, serta dengan mempunyai pengalaman dibidang keuangan sehingga sumber daya manusia tersebut mampu memahami logika akuntansi dengan baik dalam penerapan sistem akuntansi.…”
Section: Sawitri Pi and Gayatri Kejelasan Sasaran Anggaran… Pendahunclassified
“…Selain faktor penerapan SAP, kualitas informasi suatu laporan keuangan juga sangat ditentukan oleh faktor kompetensi aparatur pemerintah daerah sebagai penyusun laporan keuangan, kompetensi aparatur juga berpengaruh pada pembuatan laporan keuangan yang baik dan menggambarkan pencapaian suatu organisasi, sumber daya manusia yang berkualitas dapat meningkatkan kualitas informasi pada laporan keuangan (Nurlis & Yudiati, 2017;Dewi et al, 2019).…”
Section: Kualitas Informasi Laporan Keuangan Pemerintah Juga Tidak Terlepas Dari Penerapanunclassified